2021
DOI: 10.1080/16000889.2021.1971924
|View full text |Cite
|
Sign up to set email alerts
|

Role of river discharge and warming on ocean acidification and pCO<sub>2</sub> levels in the Bay of Bengal

Abstract: Shifts in surface ocean pCO 2 and pH are important controls governing global climate. Based on the linear relationship of observed surface pH and pCO 2 with sea surface temperature (SST), sea surface salinity (SSS) and Chlorophyll-a (Chl-a) multiple linear regression equations were developed. Based on remote sensing SST, Chl-a and model-derived SSS, pH and pCO 2 data were derived from 1998 to 2015. Overall warming of BoB is noticed at the rate of 0.004 to 0.03 C/y whereas cooling is found in the northwestern B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 81 publications
0
18
0
Order By: Relevance
“…The residual term had some impacts on diurnal pCO 2sea variability at 12:17-18:17 (Figure 10a). This might be due to the nonlinear relationship between pCO 2sea and SST or DIC (Xue et al, 2016) and factors controlling pCO 2sea , such as ubiquitous eddies (Cheng et al, 2018;Sarma et al, 2019Sarma et al, , 2020 and deposition from land and atmosphere (Sridevi and Sarma., 2021), in the BoB. Similar results were found by using Taylor-series deconvolution (Figure S13 in Supporting Information S1).…”
Section: Quantification Of Mean Diurnal Pco 2sea Variabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…The residual term had some impacts on diurnal pCO 2sea variability at 12:17-18:17 (Figure 10a). This might be due to the nonlinear relationship between pCO 2sea and SST or DIC (Xue et al, 2016) and factors controlling pCO 2sea , such as ubiquitous eddies (Cheng et al, 2018;Sarma et al, 2019Sarma et al, , 2020 and deposition from land and atmosphere (Sridevi and Sarma., 2021), in the BoB. Similar results were found by using Taylor-series deconvolution (Figure S13 in Supporting Information S1).…”
Section: Quantification Of Mean Diurnal Pco 2sea Variabilitymentioning
confidence: 99%
“…The residual term had a contribution of 2 μatm (8%) on the seasonal pCO 2sea variability, with a slightly higher contribution from March-June. This might be due to the nonlinear relationship between pCO 2sea and SST or DIC, and other factors such as calcium carbonate production/dissociation produced by coccolithophorids and foraminifera (Boehme et al, 1998) and deposition from land and atmosphere (Sridevi & Sarma, 2021). The influence of cyclonic and anticyclonic eddies on pCO 2sea cannot be ignored (Sarma et al, 2019(Sarma et al, , 2020.…”
Section: Quantification Of Seasonal Pco 2sea Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Kumar et al (1996) suggested that the BoB is a sink for atmospheric CO 2 in the 1990s whereas Sarma et al (2015; found that it is a mild source of the atmosphere due to the deposition of atmospheric pollutants. More recently Sridevi and Sarma (2021) indicated that salinity in the surface waters of the BoB is decreasing over the past two decades due to an increase in the warming of Himalayan glaciers (Goes et al, 2020). Since the pH of the Ganges and Brahmaputra River waters are relatively basic (Sarma et al, 2012), an increase in pH and a decrease in pCO 2 was noticed in the past two decades in the central and eastern BoB (Sridevi and Sarma, 2021).…”
Section: Introductionmentioning
confidence: 99%